2012
DOI: 10.1016/j.marpol.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the use of macro-algae for fuel in Ireland and the UK: An overview of marine management issues

Abstract: a b s t r a c tCompeting demand for land is driving biofuel and bioenergy research in various directions including macro-algae (seaweed). This paper reviews the main issues for the marine environment of cultivating and harvesting UK and Irish seaweed for biofuels/bioenergy, informed by stakeholder interviews. These showed stakeholders were sceptical of an offshore cultivation industry developing but generally considered inshore cultivation possible, while noting various practical obstacles and conditions. View… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…Economic viability at the most basic level for the organisation will be determined by the technological development and commercialisation of the product itself and as commercialisation is not currently close it may be a while before any certainty about this element can be sought. One of the only investigations into the economic viability of macro-algae biofuels [16] investigated the Irish and UK marine management issues associated with macro-algae cultivation and found that there was scepticism of the economic viability of farming seaweed in offshore locations but supported the development of inshore cultivation. In addition, issues have been raised by some seaweed farmers who suggest that the prices of seaweed may be too low to generate worthwhile profit [54].…”
Section: Economic Issuesmentioning
confidence: 99%
See 4 more Smart Citations
“…Economic viability at the most basic level for the organisation will be determined by the technological development and commercialisation of the product itself and as commercialisation is not currently close it may be a while before any certainty about this element can be sought. One of the only investigations into the economic viability of macro-algae biofuels [16] investigated the Irish and UK marine management issues associated with macro-algae cultivation and found that there was scepticism of the economic viability of farming seaweed in offshore locations but supported the development of inshore cultivation. In addition, issues have been raised by some seaweed farmers who suggest that the prices of seaweed may be too low to generate worthwhile profit [54].…”
Section: Economic Issuesmentioning
confidence: 99%
“…It has also been highlighted that even if local species of seaweed are used to avoid invasion of non-native species, the cultivation of seaweed at a large level might provide a source for new mutants [15]. Finally, it has also been suggested that the potential environmental impacts of transportation between cultivation and processing sites and post-processing needs to be taken into account in any environmental assessment [16].…”
Section: Environmental Issuesmentioning
confidence: 99%
See 3 more Smart Citations